Optimisasi Transportasi Pada Lingkungan Kabur Dengan Penerapan North West Corner dan Fuzzy Modified Distribution Method - Tambunan, Gilbert Pauly Hamonangan; Gultom, Parapat; Sawaluddin, Sawaluddin; Syahputra, Muhammad Romi (Universitas Islam Sumatera Utara, 2024)
Distribution of agricultural commodities to processing industries requires quite large costs. This is caused by suboptimal allocation. Optimal allocation must take into account differences in transportation distribution costs in each destination area. Pamah Village has a corn commodity, corn which is produced during the harvest season. In each harvest season, the harvest is sold to 5 collectors. From these collectors, it is marketed to 12 corn processing industries. In optimizing allocation and minimizing distribution costs, it is completed using a fuzzy approach and the North West Corner method to get an initial solution, as well as the Fuzzy Modified Distribution method to get an optimal solution. The results of this research resulted in distribution of deliveries from 5 collectors to 12 corn processing industries with a minimum total cost of Rp 1,410,507,435.00.